Exploring the community and external-agency partnership in sport-for-development programming. Issue 1 (1st January 2016) - MacIntosh, Eric; Arellano, Alexandra; Forneris, Tanya
ABSTRACT: Research question: Sport-for-development programs often rely on a community and external-agency partnership. This study explored how the community–external-agency partnership attempted to use a high cost sport of ice-hockey to create sustainable community development outcomes. Research methods : The evolution of the partnership between the external-agency Right To Play and the community of Moose Cree First Nation in the Province of Ontario, Canada is examined. Data included 35 semi-structured interviews from community ( n = 26) and external-agency ( n = 9) partnership stakeholders, combined with non-participant observations of ice-hockey clinics and organizational document reviews. Results and findings: Findings provide several insights regarding resource acquisition and flow. The study found that the choice of sport is critical to initiate desired community change. Findings also indicated several challenges in program funding, human resource management, and communication highlighting the importance of sustainable resource planning. Implications: The sport of ice-hockey acted as an initial hook to mobilize community members' interest and gain outside organizations' resources. The findings denote differences in partner objectives which can complicate the delivery of programming. Sustaining the sport of ice-hockey within the community took on a more traditional sport development outcome. Ultimately, resource availability and acquisition (tangible and intangible) within a sport-for-development partnership must be considered before embarking on a program. Articulating a sustainable strategy where the external agency has a planned withdraw date and the community can independently continue programming if deemed desirable is important. Partnerships mutually benefit when there are clearly stated and communicated objectives.